Ethics and Biosafety in Dental Care for Patients with Human Immunodeficiency Virus - Ana Ibis Betancourt García; Carlos Lázaro Nodal García; Jorge Manuel García Rodríguez; Diosky Ferrer Vilches; Elizabeth Álvarez Heredia (Medisur)
Background: the only way of contracting human immunodeficiency virus during dental treatment is through contact with the blood of an HIV-positive patient with non-intact skin or mucosa of the professional. This requires biosecurity measures to reduce the risk of crossed infection and ensure compliance of bioethical aspects to be considered when treating these patients. Objective: To determine knowledge levels of dentists on biosafety and bioethical principle of justice in the treatment of patients with human immunodeficiency virus. Methods: A cross sectional and descriptive study was conducted involving 45 professionals who worked in Stomatological clinics of three parishes in Caracas, Venezuela, from January to December 2010. The following were analyzed: knowledge on biosafety (mechanisms of disease transmission, control measures and flowchart sterilization measures before an accident) and the justice bioethical principle (time and place of treatment, instruments used and time to devote to patient). Results: The knowledge level according to the bioethical principle of justice was assessed: 40% for good, 37.7% for average and 22.2% for bad. For biosecurity measures it was obtained: 26.6% good, 24.4% average and 48.8% bad. Conclusions: knowledge level on the bioethical principle of justice and biosecurity measures to treat patients living with human immunodeficiency virus is unsatisfactory in more than half of the dentists surveyed.